Поведение клеточного центра при распластывании трансформированных фибробластов - Гудима, Г.О.; Воробьев, И.А.; Ченцов, Ю.С. (Биополимеры и клетка, 1987)
В L-клетках на всех стадиях распластывания ориентация центриолей к плоскости субстрата случайна. В суспендированных клетках происходит активация клеточного центра; рост микротрубочек за его пределы происходит только после начала распластывания клеток. В монослое не происходит инактивации клеточного центра, что отличает L-клетки от изучавшихся ранее нормальных фибробластов. В L-клітинах на всіх стадіях розпластування орієнтація центріолей до площини субстрату випадкова. У суспендованих клітинах відбувається активація клітинного центра; ріст мікротрубочок за його межі відбувається лише після початку розпластування клітин. У моношарі не відбувається інактивації клітинного центра, що відрізняє L-клітини від нормальних фібробластів, які вивчали раніше. In L-strain fibroblasts at all stages of spreading (primary attachment, radial spreading, polarization, monolayer) centrioles are randomly oriented to the substrate plane. In polarized cells centrioles are located between the nucleus and the leading edge. In suspended cells short microtubules appear near the centrioles in a number exceeding that in monolayer culture cells. The outgrowth of microtubules from the centrosome is observed in radially spread and polarized L-cells. In contrast to normal murine fibroblasts the number of long and middle microtubules radiating from the active centrioles does not differ significantly in the radially spread, polarized and monolayer culture L-cells. This fact confirms the suggestion that the orientation of centrioles perpendicular to the substrate plane which is observed during the spreading and polarization of fibroblasts is connected with the intensified growth of microtubules from the centrosome. On the basis of a comparative analysis of the centrosome behaviour in normal, slightly transformed (3T3) and strongly transformed (L) fibroblasts the orientation of the active cenlrioles perpendicular to the substrate plane and the activation of microtubule formation in the centrosome during spreading and polarization is supposed to be dependent on a degree of morphological transformation of fibroblasts.